FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN BANK KOMERSIAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2020 - widhikurniasihnurrohmah; Ahmad Muslim; Maria C. Widiastuti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims at analyzing the factors that influence of the value of commercial bank companies, including Non Performing Loan (NPL), BI Rate, inflation, liquidity, profitability, and the size of the company. The value of the company measured by Tobin's Q method. This research was conducted with a quantitative approach. The data used in this study is secondary data sourced from the financial statements of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2015-2020. The study sample was selected using the purposive sampling method so that 35 companies were sampled. Data analysis used for hypothesis tests is multiple regression analysis using the Eviews 12 program. Based on the results of study and hypothesis testing, it was concluded that non-performing loans (NPL), BI rates, inflation, liquidity, profitability, and the size of companies together have little effect on the value of commercial bank companies. Liquidity and profitability affect the company's value of commercial banks and the BI Rate, NPL, inflation and size of the company partially have no effect on the value of the commercial bank company. The results of this study inform that the increasingly small liquidity will increase the value of banking companies. A good credit policy can mitigate bad credit so as to reduce the potential for problematic credit that causes profitability and the value of the company to decline. In addition, the higher the profitability of the bank, the more attractive investors will eventually increase the value of the company.